GIS and the humanities: Presenting a path to digital scholarship with the Story Map app. Issue 2 (2nd October 2017) - Kallaher, Amelia; Gamble, Alyson
ABSTRACT: Working collaboratively, a scholarly resources librarian and a subject liaison librarian at a small, public liberal arts college have created a GIS story mapping workshop for fellow information professionals. Using GIS, the librarians are bridging the gap between humanities and sciences in a liberal arts environment. The librarians' experience of being introduced to GIS and creating training for others enabled them to support their library's data services and digital scholarship initiatives. By helping connect the humanities with science and technology using story maps, librarians can create a neutral environment for learners to conduct interdisciplinary research and develop spatial literacy.